Leaf Venation Architecture in Relation to Leaf Size Across Leaf Habits and Vein Types in Subtropical Woody Plants - Peng, Guoquan; Xiong, Yingjie; Yin, Mengqi; Wang, Xiaolin; Zhou, Wei; Cheng, Zhenfeng; Zhang, Yong-Jiang; Yang, Dongmei (Frontiers in Plant Science, 2022)
determinants of plant adaptation to environments. Leaf size is an important determinant of leaf function and ecological strategy, while leaf venation, the main structure for support and transport, determines the growth, development, and performance of a leaf. The scaling relationship between venation architecture and leaf size has been explored, but the relationship within a community and its potential variations among species with different vein types and leaf habits have not been investigated. Here, we measured vein traits and leaf size across 39 broad-leaved woody species within a subtropical forest community in China, and analyzed the scaling relationship using ordinary least squares and standard major axis method. Then we compared our results with the global dataset. The major vein density, and the ratio of major (1º and 2º) to minor (3º and higher) vein density both geometrically declined with leaf size across different vein types and leaf habits. Further, palmate-veined species have higher major vein density and the ratio of major to minor vein density at the given leaf size than pinnate-veined species, while evergreen and deciduous species showed no difference. These robust trends were confirmed by reanalyzing the global dataset using the same major vein classification as ours. We also found a tradeoff between the cell wall mass per vein length of the major vein and the major vein density. These vein scaling relationships have important implications on the optimization of leaf size, niche differentiation of coexisting species, plant drought tolerance, and species distribution.